2014
DOI: 10.1111/j.2047-6310.2014.218.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, central adiposity and cardiometabolic risk factors in children and adolescents: a family‐based study

Abstract: Objective Assess genetic and phenotypic correlations of obesity-related cardiometabolic risk factors in a family-based cohort. Methods Anthropometric, body composition and biochemical measurements were collected on 999 members of 111 extended Midwestern US families of Northern European origin. Forward stepwise regression was used to identify which of Tanner stage, sex, Tanner stage by sex, BFMI, body fat percent (BF%) (DXA), VF/SubQF (CT scan for adults or MRI for children), VF, SubQF, BMI% and waist to heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 20 publications
7
76
1
1
Order By: Relevance
“…Hormonal differences have been postulated as possible explanations (4, 27), as have behavioral factors such as differences in physical activity and sedentary behavior, however, no definitive conclusions have been reached (28, 29). Differences in body distribution of excess adiposity could be another explanation, as there are studies that suggest that visceral adiposity is a stronger influence on cardiometabolic abnormalities (30, 31). …”
Section: Discussionmentioning
confidence: 99%
“…Hormonal differences have been postulated as possible explanations (4, 27), as have behavioral factors such as differences in physical activity and sedentary behavior, however, no definitive conclusions have been reached (28, 29). Differences in body distribution of excess adiposity could be another explanation, as there are studies that suggest that visceral adiposity is a stronger influence on cardiometabolic abnormalities (30, 31). …”
Section: Discussionmentioning
confidence: 99%
“…Although not direct measures of body composition, for groups of children, high BMI and waist circumference accurately reflect high adiposity (i.e., fat mass) obtained through assessment of body composition 2126 and chronic disease markers. 21,27 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, longitudinal studies have shown that a healthy body composition in childhood and adolescence is associated with a healthier cardio-metabolic profile later on in life [14,15]. These findings have been replicated in clinical adult populations with diabetes mellitus, hypertension, metabolic syndrome, and several types of cancer [16,17].…”
Section: Introductionmentioning
confidence: 99%